Trans (bordando) trajetórias de vidas: corpos invisíveis, potencialidades e resistências de pessoas trans - Francisco, Daniele dos Santos (2020)
Despite the achievements before a society based on a cisgender constitution, the Trans theme faces several cultural, social and economic barriers, silencing their “inadequate” bodies and hurting their primordial rights: existence and freedom. The current Brazilian scenario materialized these barriers, demonstrating a war between classes, between genders, between colors between spirits and consciences through a gigantic polarization: the traditional, acceptable, kind, respectable in favor of families won through (ironically) violence, the wrong, depraved, criminal other's peaceful existence. The genuine divine violence of these demonstrators dared to remain silent through threats, weapons and fear of the existence of the “different” with refinements of Christian goodness, a curious and meaningless scenario in which, through their yes and their vote, their masculinity was proved. , heterosexuality and devotion to the traditional. Finally, these devotees from the hypocria celebrated with violence in addition to performing the same "depraved" acts of the "enemy", but in a confidential manner. Trans existence is surrounded by hypocrisy, the honest and traditional Brazil is the one that kills the most and ironically the one that most uses these bodies sexually, shutting them up after their secret acts in a fervent armed devotion that needs to be questioned. A way of coping with this scenario highlights the potential of life of the trans community, demonstrating even its contributions to the construction, continuity and improvements in social quality, showing that its existence does not consist of a social burden, different from the prejudice faced by it. So it is necessary, in addition to demonstrating the vulnerability of this group, to highlight their struggles and victories to deconstruct the counter-arguments of “victimization”. Thus, being Trans could not be a problem for society, but its own existential solution to a real condition. The methodology for developing the powers proposal consisted of the use of oral history and the method of transcreation, showing the life trajectory of the beings interviewed, being trans people. This methodology made it possible to relate relevant life passages with the theoretical foundation and legislative achievements, evidencing through these statements the compulsory heteronormativity and cisgenerity and its painful and unreal impositions. Even if there is a confrontation, the binary concept still shapes society, including the trans existence and its constant attempt to readjust to the “new genre”. Thus, this work sought to highlight the potential and achievements by promoting a discussion to demystify the trans existence, starting from those who actually live them daily. After these analyzes and discussions, there was a need for support promoted by groups and collectives based on human rights, opportunities in the labor market, in addition to social and family receptivity. This recognition could offer subsidies to dismantle shallow arguments arising from prejudices and misunderstandings typical of our "social guess".